Apache web server security with security hardening - Wibowo, Dega Surono; Ilmadina, Hepatika Zidny; Ardi, Ardi Susanto; Insani, Fariq Fadillah Gusti (SHM Publisher, 2023)
With the internet network, we can quickly get information very quickly. The information we get is not changed by people not authorized to access the system or platform. Apache is a web server often used to connect users with websites where the information is located. The more users there are, the more crimes there will be when attacking the web server by irresponsible people. Due to limited time for web administrators, to improve the security of the Apache web server, an intrusion detection system is needed that can help monitor network traffic and detect the type of attack that is occurring and then forward the notification to the mobile application in real-time, because attacks can occur at any time. Intrusion Detection is one implementation of the security hardening method for the software hardening category. The results of this research will be that the system will detect intrusion attempts based on the rules created, and users will receive notifications to the Telegram application and can see details of incoming reports such as the attacker's I.P. address, description of the intrusion, name of the security hole, time of intrusion, and payload used.